ROLE OF PAY AND PROMOTION POTENTIAL FOR NUTRITION AMONG EMPLOYEES OF POWER SECTOR IN HARYANA (International Journal of Food and Nutritional Sciences, 2022)
Both pay and promotion plays important role in every human being life. Through pay andincentives everyone purchase nutritious food. It is also very important for any organizationIncentives play important role and improves efficiency of human being. Power sectoremployees also needs rewards to improve efficiency. Being non profitable organization itneeds more and more efforts to be paid towards employees. Health and Nutrition are theimportant part of its assessment